A Case Report of Prurigo Nodularis-Like Lesions in a Patient with Lepromatous Leprosy - Siwanon Nawalerspanya; Siripan Sangmala; Kumpol Aiempanakit (Karger Publishers, 2020)
Leprosy or Hansen's disease is a chronic granulomatous infection that primarily affects the peripheral nerves and, consequently, the skin. Clinical manifestations vary from hypopigmentation to erythematous plaques, and it can present with leonine facies. We report a case of a patient with an uncommon clinical presentation of prurigo nodularis-like lesions without loss of sensation, for which two biopsy specimens demonstrated different histological subtypes. The first was the classic histology of lepromatous leprosy, whereas the other specimen revealed an atypical histoid leprosy variant pattern. This case report describes a patient with an atypical presentation of leprosy.